2021
DOI: 10.3390/cancers13174317
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensively Exploring the Mutational Landscape and Patterns of Genomic Evolution in Hypermutated Cancers

Abstract: Tumor heterogeneity results in more than 50% of hypermutated cancers failing to respond to standard immunotherapy. There are numerous challenges in terms of drug resistance, therapeutic strategies, and biomarkers in immunotherapy. In this study, we analyzed primary tumor samples from 533 cancer patients with six different cancer types using deep targeted sequencing and gene expression data from 78 colorectal cancer patients, whereby driver mutations, mutational signatures, tumor-associated neoantigens, and mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Shen et al (2022) also found that FBXW7, by promoting eye absent homolog 2 (EYA2) degradation, could reduce the tumor mesenchymal phenotype and enables increased immune cell infiltration, thereby enhancing the response to anti-PD-1 therapy in a mouse tumor model. Mutations in FBXW7 have also been associated with sensitivity or resistance to immunotherapy in endometrial and pancreatic cancers, as analyzed using gene sequencing (Lin et al, 2021). Therefore, screening for FBXW7 status as a biomarker to predict tumor patient response to treatment with immune checkpoint inhibitors (ICBs) or as a target to improve the efficacy of immunotherapy deserves further exploration.…”
Section: Regulating the Tumor Microenvironment (Tme) And Immunotherapymentioning
confidence: 99%
“…Shen et al (2022) also found that FBXW7, by promoting eye absent homolog 2 (EYA2) degradation, could reduce the tumor mesenchymal phenotype and enables increased immune cell infiltration, thereby enhancing the response to anti-PD-1 therapy in a mouse tumor model. Mutations in FBXW7 have also been associated with sensitivity or resistance to immunotherapy in endometrial and pancreatic cancers, as analyzed using gene sequencing (Lin et al, 2021). Therefore, screening for FBXW7 status as a biomarker to predict tumor patient response to treatment with immune checkpoint inhibitors (ICBs) or as a target to improve the efficacy of immunotherapy deserves further exploration.…”
Section: Regulating the Tumor Microenvironment (Tme) And Immunotherapymentioning
confidence: 99%
“…With respect to PCC, the most common mutations reported are related to RET proto-oncogene, VHL, SDHx, NF1, and MAX, whereas PGLs with an underlying muta- tion in subunit B of SDH (SDHB) are associated with a higher risk of aggressive behavior and development of metastases [14]. Moreover, the involvement of specific molecular pathways could imply the presence of PPGLs as part of syndromic presentation or even suggest bilateral tumors, the presence of metastatic disease, or pediatric onset.…”
Section: Molecular Pathways Genetics and Biochemical Phenotypementioning
confidence: 99%
“…Loss-of-function mutations in VHL lead to HIF-2α accumulation, thus promoting angiogenesis, tumor spreading, and metastasis [13]. The second cluster is mainly characterized by RET and NF1 mutations, although HRAS, transmembrane protein 127, MAX, and fibroblast growth factor receptor 1 mutations have been reported [14]. RET encodes a tyrosine kinase receptor and is physiologically involved in RAS/MAPK and PI3K/AKT transduction pathways of proliferation, survival, and angiogenesis; therefore, gain-of-function mutations in RET lead to constitutive activation and consequent deregulation of such pathways determining increased cell survival.…”
Section: Molecular Pathways Genetics and Biochemical Phenotypementioning
confidence: 99%
See 1 more Smart Citation